The role of defendant gender on juror decision-making within a mock sex trafficking case among a jury-eligible community sample. Issue 2 (4th May 2022) - Stevens, Kay Lynn; Austin, Adam; Wheeler, Deborah; Malec, Tara
ABSTRACT: Sex trafficking is considered a public health emergency, although there is public confusion about the crime. Defendant gender has been demonstrated to affect juror decision-making within crimes of sexual victimisation, but there was no known literature examining the effect of defendant gender on juror decision-making within a sex trafficking case. To address this void in the literature, we investigated the effect of defendant gender on juror decision-making in a mock sex trafficking case. A community sample of jury-eligible individuals ( n = 204) were randomly assigned to either a male or female defendant gender condition in which they read a sex trafficking mock trial summary and completed the Juror Decision Scale. The male defendant was found guilty significantly more frequently than the female defendant although the effect size was relatively small. Complainant Believability, Defendant Believability, and Decision Confidence significantly predicted verdict. Implications of these findings for the justice system are discussed. PRACTICE IMPACT STATEMENT: The importance of addressing the crime of sex trafficking is paramount; however, there was a void in the juror decision-making literature. Findings from this experimental simulation of juror decision-making in a mock sex trafficking case indicated that defendant gender plays a role in verdict formation. Juror education is recommended to reduce the effects of gender bias in sex trafficking jury trials.